2018
DOI: 10.1103/physrevlett.120.231802
|View full text |Cite
|
Sign up to set email alerts
|

Search for a Hypothetical 16.7 MeV Gauge Boson and Dark Photons in the NA64 Experiment at CERN

Abstract: We report the first results on a direct search for a new 16.7 MeV boson (X) which could explain the anomalous excess of e^{+}e^{-} pairs observed in the excited ^{8}Be^{*} nucleus decays. Because of its coupling to electrons, the X could be produced in the bremsstrahlung reaction e^{-}Z→e^{-}ZX by a 100 GeV e^{-} beam incident on an active target in the NA64 experiment at the CERN Super Proton Synchrotron and observed through the subsequent decay into a e^{+}e^{-} pair. With 5.4×10^{10} electrons on target, no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 89 publications
(102 reference statements)
2
90
0
Order By: Relevance
“…Since neutrino oscillations are not affected by flavor universal NSI, here we only consider nonuniversal flavor-conserving NSI. Also, because scenarios involving L e are heavily constrained in the low-mass region by electron beam-dump experiments [15][16][17][18][19][20], we set Q e = 0 and only consider the less constrained eletrophobic NSI. For the sake of illustration, we take the following three cases for our benchmark studies [21]:…”
Section: Introductionmentioning
confidence: 99%
“…Since neutrino oscillations are not affected by flavor universal NSI, here we only consider nonuniversal flavor-conserving NSI. Also, because scenarios involving L e are heavily constrained in the low-mass region by electron beam-dump experiments [15][16][17][18][19][20], we set Q e = 0 and only consider the less constrained eletrophobic NSI. For the sake of illustration, we take the following three cases for our benchmark studies [21]:…”
Section: Introductionmentioning
confidence: 99%
“…The viable dark photon parameter space for the neutron dark matter scenario is shown in Fig. 1 (Left) with current constraints from experiments [60,61], supernovae [62,63], and BBN [64], as well as the projected sensitivities of upcoming experiments including 2 Both the dark neutron charge radius and the possible Higgs portal give subdominant contributions to this scattering. 3 This is still subject to uncertainties given disagreements with the NPLQCD collaboration [56,57] (with a possible resolution [58]), and the calculations are in the flavor SU (3) limit.…”
Section: A Dark Neutron Dark Mattermentioning
confidence: 99%
“…In this case, it becomes an ideal resonant self-interacting dark matter to Viable dark photon parameter space for asymmetric dark hadron dark matter. Existing constraints on dark photons from experiments [60,61], supernovae [62,63], and BBN [64] are dark gray. The constraints specific to our models, namely that m γ ≤ m π 0 /2 and that the dark photon decays before SM neutrinos decouple around T ∼ 3 MeV, are in light blue and red, respectively.…”
Section: B Dark Proton and Pion Dark Mattermentioning
confidence: 99%
“…Recently, collaboration of the NA64 beam dump experiment [70] reported the first results in attempting to search for the hypothetical 17 MeV gauge boson. This showed that, for the explanation of the gauge boson Z as the 8 Be anomaly, its coupling to the electron must satisfy the following constraint…”
Section: Be Anomaly and Other Constraintsmentioning
confidence: 99%